A (Hf0.2Mo0.2Nb0.2Ta0.2Ti0.2)C system high-entropy ceramic with excellent mechanical and tribological properties prepared at low temperature. (June 2023) - Sun, Qichun; Chen, Wenyuan; Zhu, Shengyu; Cheng, Jun; Tan, Hui; Chen, Juanjuan; Guo, Jie; Yang, Jun
Abstract: It is a substantial challenge to prepare high-performance high-entropy carbides at low temperature. In this study, a system of (Hf0.2 Mo0.2 Nb0.2 Ta0.2 Ti0.2 )C high-entropy ceramics with excellent mechanical and tribological properties were prepared at low temperature by using mixture with Aluminum. The results indicate that sintering temperature of specimen with 7 wt% Aluminum (HEC7A) can be reduced by 150 °C. Meanwhile, the synergy effect of the solid solution hardening and grain refinement enables the samples with a higher microhardness (≥18.1 GPa). Moreover, the addition of Aluminum can enhance the wear resistance. Especially for HEC7A at 900 °C, the wear rate is three times less than that of the pure sample. The primary anti-wear mechanism is the formation of Al2 O3 tribo-films by the tribo-chemical reaction. Highlights: High-performance (Hf0.2 Mo0.2 Nb0.2 Ta0.2 Ti0.2 )C system high-entropy ceramics were prepared. Using mixture with Al can reduce the sintering temperature and grain size of samples. Solid solution hardening and grain refinement make samples with a higher hardness. Fracture toughness and tribological property are effectively enhanced by addition Al. The anti-wear mechanism is formation of Al2 O3 tibo-film by the tribo-chemical reaction.